Integração de bioprocessos para a estabilização de resíduos agroindustriais - Niedzialkoski, Rosana Krauss (2020)
The use of waste generated in the broiler production chain, given its significant amount, is a strategic issue and refers to the sustainability of the productive sector. Currently, composting is the most used process to stabilize these wastes. Furthermore, they have the potential for energy production through anaerobic digestion (AD) and can be subjected to the vermicomposting process, provided that some factors are observed. The present study evaluated the integration of bioprocesses to increase the possibilities of using waste from the broiler chicken production. For this, composting windrows were subjected, at different times (T0, T10, T20 and T30 days), to the separation of the solid-liquid fractions (SF) after being submerged in water (2:1, water: waste, by weight in natural matter). After 24h in aqueous environment, part of the solid material retained in the sieve was again lined up for the completion of the composting process; another part of the solid fraction was subjected to vermicomposting and the liquid fraction was sent to AD. The performance of the composting process was evaluated according to the temperature and mass and volume reductions, and the obtained compounds were evaluated for physical-chemical and spectroscopic characteristics and suitability as a substrate for the production of tomato seedlings after the stabilization phase (65 days) and maturation (95 days). At the end of the vermicomposting, the qualitative and spectroscopic characteristics of the vermicomposites and the number of eggs, young and adult worms were evaluated. The liquid fraction was characterized and the biochemical methane potential (BPM) was evaluated. SF interference was observed in some control parameters of the composting process. The windrows that were not submitted to SF (control) showed greater exothermic accumulation (1053°C) when compared to the other windrows. However, SF did not affect the minimum time (15 days) for sanitizing the process, that is, temperatures greater than or equal to 55ºC. The principal component analysis (PCA) revealed the existence of two distinct groups, stabilized and matured, in terms of physicalchemical characteristics. However, when evaluated for use suitability as a substrate, it was observed that organic compounds from windrows that were subjected to SF enabled higher quality tomato seedlings (QIS), regardless of the stage of the compost (stabilized or matured). Composting followed by hydration and SF as pre-treatment before vermicomposting, favored the earthworms’ adaptation and survival by reducing the salt, total organic carbon, and nitrogen content. Multivariate analysis showed that these variables, in high concentration, could limit vermicomposting. In addition to providing a favorable environment for the development of earthworms, the integration of bioprocesses generated, at the end, a quality organic fertilizer, free of phytotoxic compounds and with a phyto-stimulating character. The best condition for recovering energy from the liquid fraction was the T0 treatment with 461.8 L CH4 kg-1 .SVadd, with pre-composting period not exceeding 20 days. The conclusion was that the integration of the composting, vermicomposting and AD bioprocesses is a sustainable alternative, since it allows not only the recycling of nutrients of the waste, but also the generation of a clean energy source.